Analisis Permintaan Rumah Tangga Terhadap Daging Ayam Broiler Di Kabupaten Mempawah - Imelda, Eko Sasongko Adi, Nurliza, (Jurnal Social Economic of Agriculture, 2017)
The population growth and improvement of living standard as well as public awareness of quality food and nutrition will lead to a rise in demand for protein-based foods, especially from broiler meat. The objective of the research was to analyze the factors that influence household demand for broiler meat in Mempawah District.  The research was conducted by descriptif method since Desember 2015 to January 2016.  The primary data were collected by observation and interview with 100 respondent who were directly purchasing broiler product were drawn randomly from traditional markets in Mempawah Hilir, Sui Pinyuh and Siantan sub-district. Secondary data were obtained from the interrelated institusion. Primary data analyzed by the ordinary least squares method (OLS) with Eviews7 program. The results showed that the main determinant of broiler meat demand are own price, household income and number of household.  The valus of own-price elasticity of broiler meat demand is more than one that mean elastic. The value of income elasticity of meat demand is positive and less than one that indicated inelastic, it means that the broiler was normal goods.Keywords : broiler meat, elasticity, OLS, demand, household